2013
DOI: 10.1371/journal.pone.0074410
|View full text |Cite
|
Sign up to set email alerts
|

New Measure of Insulin Sensitivity Predicts Cardiovascular Disease Better than HOMA Estimated Insulin Resistance

Abstract: ContextAccurate assessment of insulin sensitivity may better identify individuals at increased risk of cardio-metabolic diseases.ObjectivesTo examine whether a combination of anthropometric, biochemical and imaging measures can better estimate insulin sensitivity index (ISI) and provide improved prediction of cardio-metabolic risk, in comparison to HOMA-IR.Design and participantsHealthy male volunteers (96 Chinese, 80 Malay, 77 Indian), 21 to 40 years, body mass index 18−30 kg/m2. Predicted ISI (ISI-cal) was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
10
1
2
Order By: Relevance
“…HOMA-IR, which is a computation based on fasting insulin and glucose values, represents the most common surrogate measure of insulin resistance. 39 It has a moderate correlation with insulin sensitivity, which is likely why it was not statistically significant in our study. We also found that participants taking adjunctive lithium or valproate had higher average body mass index of approximately 3.28 units (kg/m 2 ) compared with those not taking lithium or valproate, although this relationship did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 61%
“…HOMA-IR, which is a computation based on fasting insulin and glucose values, represents the most common surrogate measure of insulin resistance. 39 It has a moderate correlation with insulin sensitivity, which is likely why it was not statistically significant in our study. We also found that participants taking adjunctive lithium or valproate had higher average body mass index of approximately 3.28 units (kg/m 2 ) compared with those not taking lithium or valproate, although this relationship did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 61%
“…Regardless of diabetes status, degree of insulin resistance is associated with future CV events 125, 126 and severity of MI. 127 An elevated insulin response to sugar (an oral glucose load) has been found in patients with atherosclerosis of the peripheral, cerebral, and coronary arteries, 128, 129 and insulin levels following a glucose challenge have been independently associated with MI occurrence 130 and CHD mortality.…”
Section: Sugar and Chd Events And Mortalitymentioning
confidence: 99%
“…3 Insulin resistance is associated with hyperinsulinemia, a condition that may promote abdominal-fat storage, increased triglyceride levels, and other metabolic disturbances 4 dall part of a broader metabolic syndrome 5 that is sometimes referred to as insulin-resistance syndrome. Markers of insulin resistance predict future cardiovascular (CV) risk, 6,7 with hyperinsulinemia being an independent risk factor for coronary heart disease. 8,9 Individuals with insulin-resistant (ie, type 2) diabetes have a life expectancy 5 to 10 years shorter than those unaffected by the disease, with much of the difference due to CV causes.…”
mentioning
confidence: 99%